Ultrasound-Enhanced Subcritical Fluid Extraction of Essential Oil from Nymphaea alba var and Its Antioxidant Activity. (3rd December 2019) - Zhao, Ying; Fan, Yang-Yang; Yu, Wen-Gang; Wang, Jian; Lu, Wenju; Song, Xi-Qiang
Abstract: Background: The essential oil content of the water lily is extremely low; thus, finding a new method that can extract essential oil from water lilies with a high extraction rate and no residual organic solvents is essential. Objective: The optimal processing conditions for the ultrasound-enhanced subcritical fluid extraction of essential oil from Nymphaea alba var (red water lily) and the antioxidant activity of the essential oil in vitro are investigated to provide theoretical bases for identification and development. Methods: Single-factor experiments and orthogonal designs are performed to determine the effects of extraction conditions on essential oil yields. The chemical composition of essential oil is analyzed using GC–MS. Results: The optimum extraction parameters are established as follows: extraction temperature, 35°C; extraction time, 30 min/time for four times; ratio of material to liquid, 1:3; ultrasound power, 250 W/L; and ultrasonic frequency, 20 kHz. The extraction rate of essential oil is 0.315% under these conditions. Eleven components comprise more than 1% content. The main chemical constituents are 8-hexadecyne (31.04%) and 2, 6, 10-trimethyl-tetradecane (3.95%). The essential oil from N. alba var has an antioxidant activity in vitro; however, its antioxidant activity is weaker than that of butylated hydroxytoluene. Conclusions: Subcritical fluid is suitable for the extraction of essential oil from N. alba var, and the essential oil has a good antioxidant activity. Highlights: The essential oil content of N. alba var is 0.315%. Forty-seven chemical constituents are identified and isolated from N. alba var and analyzed by GC–MS.